Hypertension Response after Stenting adult with Coarctaion of Aorta One Year Follow Up - Ali Yahya Abdullah Alsallami; Ahmed Abdulzahra Jeyad; Basim Abd Ali Saeed; Hassan Ali Essa Al Mamuri (Institute of Medico-legal Publications Pvt Ltd, 2021)
Coarctaion of aorta occur in 6 % of patient with congenital heart disease, balloon dilation ,stenting andsurgery have been proved as modality of treatment coarctaion of aorta.Usually untreated coarctation of aortamay lead to renal, vascular and cardiac complication that start to appear at binging of fourth decade of life.Toknew hypertension response after stenting adult with coarctation of aorta. 75 patients with coarctaion of aorta30 male (40%) and 45 female (60 %) was involve in this prospective longitudinal study, there age range from16 to 41 year, for all echocardiography, CT chest done to confirm diagnosis then all undergo catheterizationof aorta with 2 sheath one femoral and other radial to measure pressure gradient across stenosis and stentlocalization follow by stenting with pre and post dilation if needed then measure pressure gradient acrossstent. All patients stent by uncover stent including for 2 case with interrupted coarctaion, immediately afterstent pressure gradient fall almost all our patient then follow up 6 month, 1 year by angiography assessmentwith CT chest show no stent fracture or aneurysm in aorta at stent site. The study conclude uncovered stentappear to be safe in treating coarctaion of aorta with less morbidity and mortality. stent adult with coarctaionof aorta have advantage of lowering blood pressure in those suffer from hypertension.